A method for preparing nano titanium nitride and prepared nano titanium nitride
The preparation of nanotitanium nitride particles by sol-gel method solves the problems of complex process, high cost and unstable finished product quality in the prior art, and achieves high purity, good dispersion and low cost preparation of nanotitanium nitride.
Patent Information
- Application Number
- CN202111151423.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-09-29
AI Technical Summary
The existing methods and processes for preparing nanotitanium nitride have high requirements, high raw material costs, low nitrogen content of the product, and low yield of the finished product.
The nanotitanium nitride particles are prepared by sol-gel. The specific steps include mixing the titanium-containing compound with the starch material to form a mesh colloid, and then heating and insulating it in a nitrogen atmosphere to generate nanotitanium nitride particles and obtaining the final product by removing residual carbon.
It realizes high purity and good powder dispersion of nano-titanium nitride particles, stable process, simple operation, low raw material cost, and can be mass-produced on existing equipment, reducing equipment cost.
Smart Images

Figure CN115872369B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a method for preparing nano titanium nitride and the prepared nano titanium nitride. Background Art
[0002] Nano-titanium nitride is a golden or black powder and is widely used in conductive materials, cemented carbide, high-temperature ceramic materials and other fields.
[0003] At present, the preparation method of nano titanium nitride mainly uses sponge titanium as raw material and nitrogen as nitrogen source to produce titanium nitride powder by nitriding. However, this method has high process requirements, high raw material costs, low nitrogen content in the product, and low finished product yield. Summary of the invention
[0004] The embodiment of the present invention provides a method for preparing nano titanium nitride and the prepared nano titanium nitride, and the nano titanium nitride particles are prepared by a sol-gel method, which has the advantages of good powder dispersibility, high purity, easy reaction control, stable process, and simple process operation. At the same time, the raw material cost is low, and the existing production equipment can be used for batch rapid production, further reducing the equipment cost.
[0005] In a first aspect, an embodiment of the present invention provides a method for preparing nano titanium nitride, the method for preparing nano titanium nitride comprising:
[0006] The titanium-containing compound is dissolved in water to prepare a solution with a mass concentration of 5% to 30%, starch material is added in proportion, and stirred until uniform to obtain a first solution;
[0007] The first solution is placed in a preparation device, heated to 80°C to 120°C, and kept warm for 10min to 30min, so that the starch molecules in the starch material are gelatinized to form a network-shaped colloid containing titanium ions, and then the obtained colloid is dried at 60°C to 80°C to obtain a dry colloid;
[0008] The dried colloid is heated to 700° C. to 1200° C. at a rate of 1° C. / min to 10° C. / min in a nitrogen atmosphere, and kept at this temperature for 1 to 10 hours to obtain a carbon matrix containing titanium nitride;
[0009] The carbon matrix containing titanium nitride is heated to 400°C to 500°C in an air atmosphere or an oxygen atmosphere and kept warm for 24 to 48 hours, or is heated to 700°C to 1000°C in a carbon dioxide atmosphere and kept warm for 10 to 24 hours, and carbon oxides are generated by reaction to remove residual carbon in the carbon matrix containing titanium nitride. The sample is then washed, filtered and dried to obtain the nano titanium nitride particles.
[0010] Preferably, the titanium-containing compound specifically includes any one or more of titanyl sulfate, titanium trichloride, titanium tetrachloride, and titanium iodide.
[0011] Preferably, the starch material specifically includes one or more combinations of corn starch, potato starch, tapioca starch or other starch raw materials that can form starch gelatinization colloid.
[0012] Preferably, in the first solution, the mass ratio of titanium ions in the titanium-containing compound to starch molecules in the starch material is 1:2 to 1:20.
[0013] Preferably, the stirring until uniform is specifically: stirring at a rotation speed of 100 r / min to 700 r / min until uniform.
[0014] In a second aspect, an embodiment of the present invention provides nano titanium nitride prepared by the method for preparing nano titanium nitride according to the first aspect.
[0015] Preferably, the particle size of the nano titanium nitride is between 5 nm and 500 nm.
[0016] The method for preparing nano titanium nitride provided in the embodiment of the present invention prepares nano titanium nitride particles by a sol-gel method, and the obtained product has the characteristics of good powder dispersibility and high purity; during the preparation process, the reaction is easy to control, the process is stable, the process operation is simple, and the raw material cost is low. It can also be produced in batches quickly using currently available production equipment, further reducing the equipment cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0018] Figure 1 A flow chart of a method for preparing nano titanium nitride provided in an embodiment of the present invention;
[0019] Figure 2 A scanning electron microscope (SEM) image of nano-titanium nitride provided in Example 1 of the present invention;
[0020] Figure 3 This is the X-ray diffraction (XRD) diagram of nano-titanium nitride provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The present invention is further described below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0022] The present invention proposes a method for preparing nano titanium nitride, the main steps of which are as follows: Figure 1 As shown, including:
[0023] Step 110, dissolving the titanium-containing compound in water to prepare a solution with a mass concentration of 5% to 30%, adding starch material in proportion, and stirring until uniform to obtain a first solution;
[0024] Specifically, the titanium-containing compound includes any one or more of titanyl sulfate, titanium trichloride, titanium tetrachloride, and titanium iodide, and titanyl sulfate is preferably selected.
[0025] The starch material may specifically be a combination of one or more of corn starch, potato starch, tapioca starch or other starch raw materials that can form starch gelatinization colloid.
[0026] In the first solution, the mass ratio of titanium ions in the titanium-containing compound to starch molecules in the starch material is 1:2 to 1:20.
[0027] During the stirring process, the stirring speed is 100r / min to 700r / min, and the mixture is stirred thoroughly until uniform.
[0028] Step 120, placing the first solution in a preparation device, heating it to 80° C. to 120° C., and keeping it warm for 10 min to 30 min, so that the starch molecules in the starch material are gelatinized to form a network-shaped colloid containing the titanium ion solution, and then drying the obtained colloid at 60° C. to 80° C. to obtain a dry colloid;
[0029] Specifically, the preparation device can adopt existing equipment, such as a vermicelli machine.
[0030] In the implementation process of the present invention, the screw conveying time of the vermicelli machine is 10 minutes to 30 minutes, and the heating temperature ranges from 80°C to 120°C.
[0031] Step 130, heating the dried colloid to 700°C to 1200°C at 1°C / min to 10°C / min in a nitrogen atmosphere, and keeping the temperature for 1 hour to 10 hours to obtain a carbon matrix containing titanium nitride;
[0032] Step 140, heating the carbon matrix containing titanium nitride to 400°C to 500°C in an air atmosphere or an oxygen atmosphere, and keeping it warm for 24 to 48 hours, or heating it to 700°C to 1000°C in a carbon dioxide atmosphere, and keeping it warm for 10 to 24 hours, to remove the residual carbon in the carbon matrix containing titanium nitride by reacting to generate carbon oxides, and then washing, filtering and drying the sample to obtain nano titanium nitride particles.
[0033] Specifically, in an air atmosphere or an oxygen atmosphere at 400°C to 500°C, carbon oxides are generated by an oxidation reaction of carbon to remove residual carbon in a carbon matrix containing titanium nitride. At the same time, at this reaction temperature, the chemical bonds in titanium nitride will not be destroyed, so nano titanium nitride particles can be finally obtained.
[0034] In a carbon dioxide atmosphere at 700°C to 1000°C, carbon dioxide and carbon form carbon oxides, which can also remove residual carbon in the carbon matrix containing titanium nitride.
[0035] These two methods of removing residual carbon can be used one by one according to actual conditions in specific implementation.
[0036] The particle size of the prepared nano titanium nitride is between 5nm and 500nm.
[0037] In order to better understand the technical solution provided by the present invention, the specific process of preparing nano titanium nitride by the method provided by the above embodiment of the present invention is described below with multiple specific examples.
[0038] Example 1
[0039] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0040] Step 1: Take 200g of titanium oxysulfate and add 466ml of water to dissolve to prepare a 30% solution, add 300g of corn starch, and stir at a speed of 100r / min until it is uniform.
[0041] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 80°C, and keep it warm for 30 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 60°C to obtain a dry colloid.
[0042] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 700°C at a rate of 1°C / min and kept at that temperature for 10 hours to obtain a carbon matrix containing titanium nitride.
[0043] Step 4: heating the carbon matrix containing titanium nitride obtained in step 3 to 500° C. in an air atmosphere and keeping the temperature for 10 hours to remove residual carbon in the sample, washing, filtering and drying the sample to obtain the nano titanium nitride particles.
[0044] Figure 2 This is a scanning electron microscope (SEM) image of nano-titanium nitride provided in Example 1 of the present invention. The SEM image shows that the prepared particles are all at the nanometer level and have a spherical shape; Figure 3This is the X-ray diffraction (XRD) diagram of nano titanium nitride provided in Example 1 of the present invention; XRD shows that the characteristic peak T is titanium nitride, and there are no other impurity peaks.
[0045] Example 2
[0046] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0047] Step 1: Take 200g of titanium oxysulfate and add 3800ml of water to dissolve it to prepare a 5% solution, add 1200g of corn starch, and stir it at 700r / min until it is uniform.
[0048] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 10 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0049] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 1200°C at a rate of 10°C / min and kept at that temperature for 1 hour to obtain a carbon matrix containing titanium nitride.
[0050] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 400° C. in an air atmosphere and kept warm for 48 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0051] Example 3
[0052] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0053] Step 1: Take 200g of titanium oxysulfate and add 800ml of water to dissolve it to prepare a 20% solution, add 800g of corn starch, and stir at a speed of 500r / min until it is uniform.
[0054] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 100°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 70°C to obtain a dry colloid.
[0055] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 1000°C at a rate of 3°C / min and kept at that temperature for 5 hours to obtain a carbon matrix containing titanium nitride.
[0056] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 1000° C. in a carbon dioxide atmosphere and kept warm for 10 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0057] Example 4
[0058] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0059] Step 1: Take 200g of titanium oxysulfate and add 1400ml of water to dissolve it to prepare a solution with a concentration of 14.3%, add 800g of cassava starch, and stir it at a speed of 500r / min until it is uniform.
[0060] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0061] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 950°C at a rate of 3°C / min and kept at that temperature for 8 hours to obtain a carbon matrix containing titanium nitride.
[0062] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 700° C. in a carbon dioxide atmosphere and kept warm for 24 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0063] Example 5
[0064] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0065] Step 1: Take 200g of titanium oxysulfate and add 1400ml of water to dissolve it to prepare a solution with a concentration of 14.3%, add 400g of potato starch, and stir it at a speed of 500r / min until it is uniform.
[0066] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0067] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 900°C at a rate of 5°C / min and kept at that temperature for 6 hours to obtain a carbon matrix containing titanium nitride.
[0068] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 500° C. in an air atmosphere and kept warm for 48 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0069] Example 6
[0070] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0071] Step 1: Take 200g of titanium oxysulfate and add 2000ml of water to dissolve it to prepare a 9% solution, add 200g of potato starch, and stir it at a speed of 200r / min until it is uniform.
[0072] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0073] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 800°C at a rate of 5°C / min and kept at that temperature for 5 hours to obtain a carbon matrix containing titanium nitride.
[0074] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 700° C. in a carbon dioxide atmosphere and kept warm for 12 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0075] Example 7
[0076] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0077] Step 1: Take 200g of titanium oxysulfate and add 800ml of water to dissolve it to prepare a 20% solution, add 500g of pea starch, and stir at 700r / min until it is uniform.
[0078] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 100°C, and keep it warm for 30 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0079] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 800°C at a rate of 3°C / min and kept at that temperature for 5 hours to obtain a carbon matrix containing titanium nitride.
[0080] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 1000° C. in a carbon dioxide atmosphere and kept warm for 12 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0081] Example 8
[0082] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0083] Step 1: Take 200g of titanium oxysulfate and add 600ml of water to dissolve it to prepare a 25% solution, add 1000g of pea starch, and stir it at a speed of 300r / min until it is uniform.
[0084] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0085] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 950°C at a rate of 3°C / min and kept at that temperature for 8 hours to obtain a carbon matrix containing titanium nitride.
[0086] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 950° C. in a carbon dioxide atmosphere and kept warm for 20 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0087] Example 9
[0088] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0089] Step 1: Take 200g of titanium oxysulfate and add 1400ml of water to dissolve it to prepare a solution with a concentration of 14.3%, add 1000g of potato starch, and stir it at a speed of 500r / min until it is uniform.
[0090] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0091] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 950°C at a rate of 3°C / min and kept at that temperature for 8 hours to obtain a carbon matrix containing titanium nitride.
[0092] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 800° C. in an air atmosphere and kept warm for 20 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0093] Example 10
[0094] This embodiment provides a method for preparing nano titanium nitride, comprising:
[0095] Step 1: Take 200g of titanium oxysulfate and add 2000ml of water to dissolve it to prepare a 9% solution, add 600g of corn starch, and stir it at a speed of 100r / min until it is uniform.
[0096] Step 2: Put the solution stirred evenly in step 1 into a vermicelli machine, heat it to 120°C, and keep it warm for 20 minutes. The starch molecules are gelatinized in this process to form a network of colloid containing titanium ion solution. The obtained sample is completely dried at 80°C to obtain a dry colloid.
[0097] Step 3: Place the dry colloid obtained in step 2 under N 2 The temperature was raised to 950°C at a rate of 3°C / min and kept at that temperature for 5 hours to obtain a carbon matrix containing titanium nitride.
[0098] Step 4: The carbon matrix containing titanium nitride obtained in step 3 is heated to 800° C. in a carbon dioxide atmosphere and kept warm for 30 hours to remove residual carbon in the sample. The sample is washed, filtered and dried to obtain nano titanium nitride particles.
[0099] The method for preparing nano titanium nitride provided in the embodiment of the present invention prepares nano titanium nitride particles by a sol-gel method, and the obtained product has the characteristics of good powder dispersibility and high purity; during the preparation process, the reaction is easy to control, the process is stable, the process operation is simple, and the raw material cost is low. It can also be produced in batches quickly using currently available production equipment, further reducing the equipment cost.
[0100] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing nano titanium nitride, characterized in that: The preparation method of the nano titanium nitride is a sol-gel method, comprising: The titanium-containing compound is dissolved in water to prepare a solution with a mass concentration of 5% to 30%, and a starch material that can form a starch gelatinized colloid is added in proportion, and stirred until uniform to obtain a first solution; the titanium-containing compound specifically includes any one or more of titanium oxysulfate, titanium trichloride, titanium tetrachloride, and titanium iodide; The first solution is placed in a preparation device, heated to 80°C to 120°C, and kept warm for 10min to 30min, so that the starch molecules in the starch material are gelatinized to form a network colloid, and then the obtained colloid is dried at 60°C to 80°C to obtain a dry colloid; The dried colloid is heated to 700° C. to 1200° C. at a rate of 1° C. / min to 10° C. / min in a nitrogen atmosphere, and kept at this temperature for 1 to 10 hours to obtain a carbon matrix containing titanium nitride; The carbon matrix containing titanium nitride is heated to 400°C to 500°C in an air atmosphere or an oxygen atmosphere and kept warm for 24 to 48 hours, or is heated to 700°C to 1000°C in a carbon dioxide atmosphere and kept warm for 10 to 24 hours, and carbon oxides are generated by reaction to remove residual carbon in the carbon matrix containing titanium nitride. The sample is then washed, filtered and dried to obtain the nano titanium nitride particles.
2. The preparation method according to claim 1, characterized in that: The starch material specifically includes a combination of one or more of corn starch, potato starch and tapioca starch.
3. The preparation method according to claim 1, characterized in that: In the first solution, the mass ratio of titanium ions in the titanium-containing compound to starch molecules in the starch material is 1:2 to 1:
20.
4. The preparation method according to claim 1, characterized in that: The stirring until uniform is specifically: stirring at a speed of 100 r / min to 700 r / min until uniform.
5. Nano-titanium nitride prepared by the method for preparing nano-titanium nitride according to any one of claims 1 to 4.
6. The nano titanium nitride according to claim 5, characterized in that: The particle size of the nano titanium nitride is 5nm to 500nm.
Citation Information
Patent Citations
Method for preparing anatase phase titanium oxide nano particles by high-temperature treatment
CN101205083A
Method for preparing TiCN powder by using TiOSO4 and starch as Ti source and C source respectively
CN103387216A
Nanometer titanium nitride powder preparation method
CN103864030A
Sol-gel method for preparing submicron-order titanium nitride powdery material
CN105836718A
Preparation method of blocky titanium carbide, titanium nitride or titanium carbonitride aerogel
CN111892420A